Phylogenetic and genomic characterization of a novel atypical porcine pestivirus in China. Issue 1 (14th July 2017) - Zhang, H.; Wen, W.; Hao, G.; Hu, Y.; Chen, H.; Qian, P.; Li, X.
Summary: Atypical porcine pestivirus (APPV) has been considered a novel pestivirus and causative agent of congenital tremor type A‐II. An APPV CH‐GX2016 strain was characterized from newly born piglets with clinical symptoms of congenital tremor in Guangxi, China. The genome of APPV CH‐GX 2016 strain was 11, 475 bp in length and encoded a polyprotein composed of the 3, 635 amino acids. This genome sequence exhibited 88.0% to 90.8% nucleotide sequence homology with other APPV reference sequences in GenBank. Phylogenetic analysis further showed that APPV CH‐GX is a novel pestivirus compared with previously described classical pestivirus strains. Therefore, APPV is present in pigs in China.